Enhanced proton transport properties of Nafion via functionalized halloysite nanotubes. (4th October 2018) - Ressam, Ibtissam; El Kadib, Abdelkrim; Lahcini, Mohammed; Luinstra, Gerrit A.; Perrot, Hubert; Sel, Ozlem
Abstract: The introduction of naturally occurring fibrillary structured halloysite clays (HNTs) into the Nafion matrix resulted in an enhanced proton conductivity and a reduced activation energy for proton transport. To assess the effect of the various states of the HNTs as a membrane additive, the σH + of the composite membranes (Nafion/HNTs, Nafion/HNTs-NH2, Nafion/HNTs-SO3 H) was measured at 30 °C and 80 °C and at different levels of relative humidity (%RH). An overall improvement of the σH + of the Nafion was observed in the presence of the nanotubular additives (HNTs or HNTs-NH2 ) which can be attributed to the high specific surface area accommodating hydrophilic functional groups and therefore contributing to the water retention/management in the composite membrane. However, the Nafion/HNT-SO3 H composites are distinguished in terms of enhanced performance in σH + which persist in the whole range of % RH levels and noted that the σH + values are almost 2 times higher than native Nafion in the low humidity region (30%–50%) and at 80 °C. In agreement with the σH + enhancement, the activation energy is lower than that of native Nafion indicating that the proton transport is facilitated in the presence of -SO3 H modified HNTs, probably due to an improved connectivity and arrangement of ionic conducting domains. Highlights: Naturally occurring halloysites were functionalized with –NH2 and –SO3 H groups. The introduction of functionalized halloysite nanotubes enhances the σH + of Nafion. The σH + values are 2 times higher than Nafion, also in the low humidity (30%–50%). In line with the σH + enhancement, the Ea is lower than that of pristine Nafion.